Relative Severity of Common Human Coronaviruses and Influenza in Patients Hospitalized With Acute Respiratory Infection: Results From 8-Year Hospital-Based Surveillance in Quebec, Canada. (6th August 2020) - Gilca, Rodica; Carazo, Sara; Amini, Rachid; Charest, Hugues; De Serres, Gaston
Abstract: Background: Few data exist concerning the role of common human coronaviruses (HCoVs) in patients hospitalized for acute respiratory infection (ARI) and the severity of these infections compared with influenza. Methods: Prospective data on the viral etiology of ARI hospitalizations during the peaks of 8 influenza seasons (from 2011–2012 to 2018–2019) in Quebec, Canada, were used to compare patients with HCoV and those with influenza infections; generalized estimation equations models were used for multivariate analyses. Results: We identified 340 HCoV infections, which affected 11.6% of children (n = 136) and 5.2% of adults (n = 204) hospitalized with ARI. The majority of children (75%) with HCoV infections were also coinfected with other respiratory viruses, compared with 24% of the adults ( P < .001). No deaths were recorded in children; 5.8% of adults with HCoV monoinfection died, compared with 4.2% of those with influenza monoinfection ( P = .23). The risk of pneumonia was nonsignificantly lower in children with HCoV than in those with influenza, but these risks were similarly high in adults. Markers of severity (length of stay, intensive care unit admissions, and case-fatality ratio) were comparable between these infections in multivariate analyses, in both children and adults. Conclusions: In children and adults hospitalized with ARI, HCoV infections were less frequent than influenza infections, but were as severe as influenza monoinfections. Abstract : Common human coronaviruses were less frequent than influenza in children and adults hospitalized with acute respiratory infections but generated significant morbidity. Length of stay, intensive care unit admissions, and case-fatality ratio were comparable for both types of monoinfection.